Corrigendum to "Solubility measurement and modelling of 1, 8-dinitronaphthalene in nine organic solvents from T = (273.15 to 308.15) K and mixing properties of solutions" [J. Chem. Thermodyn. 90 (2015) 259–269]. (December 2017) - Yang, Zehui; Shao, Danfeng; Zhou, Guoquan
Abstract: The solubility data of 1, 8-dinitronaphthalene in nine organic solvents at various temperatures and mixing properties of solutions were reported by our group ( J. Chem. Thermodyn. 90 (2015) 259–269). The numerical values of the activity coefficients for 1, 8-dinitronaphthalene dissolved in nine solvents of the published paper was incorrectly evaluated by our group. In addition, some flaws were identified regarding our calculation of the mixing thermodynamic properties by Wilson model, especially for infinitesimal concentration reduced excess enthalpy. The relevant mathematical errors were corrected.